A systematic review of shock-attenuating componentry for lower limb amputees. (August 2018) - Farrar, Mitchell; Thomas, Emma
Background: Shock-attenuating pylons are commonly fitted to prostheses in order to compensate for the anatomical and biomechanical shock-absorbing features of the lower limb removed upon amputation. However, studies concerning their shock-attenuating capacity are highly variable and, to date, have not yet been reviewed, making them difficult to interpret and apply in clinical practice. Objectives: To synthesise and appraise the available literature examining the effectiveness of shock-attenuating pylons in attenuating shock upon limb loading compared to rigid pylons among lower limb amputees. Study design: Systematic review. Methods: A comprehensive search of seven databases was conducted using search terms concerning amputation level, shock-attenuating and rigid pylons as well as measures of shock attenuation. All studies yielded were screened against established inclusion and exclusion criteria before eligible articles were appraised using the Quality Assessment Standard for Crossover Studies adapted from the Cochrane handbook. Results: Nine articles were eligible for inclusion. While there was a trend among studies to indicate only a limited positive effect of shock-attenuating pylons in attenuating transient impact forces, limitations to the study designs, namely, in sampling, poor reporting of methodological details and heterogeneity of outcomes made conclusive interpretation of results difficult. Conclusion: While the current body of literature does not reconcile with claims made by manufacturers of shock-attenuating pylons, it is insufficient to conclusively determine how effective shock-attenuating pylons are, in comparison with conventional rigid pylons, in attenuating transient impact forces among lower limb amputees. Higher quality research is required to better guide decisions regarding prescription of shock-attenuating componentry in clinical practice. Clinical relevance: When delivered well, research can provide clinicians with objective and reliable data that can be applied in their practice to guide prescription of componentry. However, methodological limitations to research may compromise the reliability of findings, thereby producing potentially misleading outcomes. These limitations must be recognised and appreciated such that findings may be interpreted accurately and applied appropriately.